Decrease in Multidrug Resistance-associated Protein 2 Activities by Knockdown of Phosphatidylinositol 4-phosphate 5-kinase in Hepatocytes and Cancer Cells - Atsushi Kawase; Yuta Inoue; Miho Hirosoko; Yuka Sugihara; Hiroaki Shimada; Masahiro Iwaki (Frontiers Media S.A., 2019)
Purpose: The plasma membrane localization and transport activity of multidrug resistance-associated protein 2 (MRP2/ABCC2) and P-glycoprotein (P-gp/ABCB1) efflux transporters are governed by transporter-associated proteins. Phosphatidylinositol 4,5-bisphosphate (PIP2) formed by phosphatidylinositol 4-phosphate 5-kinase type 1 (PIP5K1) activates the linker function of radixin for efflux transporters. Radixin is involved in the plasma membrane localization of efflux transporters. We examined whether PIP5K1 could be a target for the modulation of transporter activities in hepatocytes and cancer cells. Methods: The effects of PIP5K1 depletion by siRNA in mouse primary hepatocytes, PANC1 human pancreatic carcinoma cells, and HepG2 human hepatocellular carcinoma cells on the intracellular accumulation of MRP2 and P-gp substrates were examined. Results: PIP5K1A depletion resulted in increased intracellular accumulation of carboxydichlorofluorescein, a MRP2 fluorescent substrate, in mouse primary hepatocytes, PANC1 cells, and HepG2 cells. In PANC1 and HepG2 cells, the transport activities of MRP2 were significantly decreased by PIP5K1C depletion. However, the transport activities of P-gp were unchanged by PIP5K1 depletion. PIP2 levels were unchanged between control and PIP5K1A- or PIP5K1C-depleted HepG2 cells. MRP2 mRNA levels showed few changes in HepG2 cells following PIP5K1A or PIP5K1C depletion. The expression of phosphorylated radixin was decreased by PIP5K1A and PIP5K1C depletion, although total radixin levels were unchanged. Conclusions: These data suggest that PIP5K1A and PIP5K1C could be target proteins for modulating MRP2 function, partly because of the resulting changes of the linker function of radixin.